Analysis of data based on clinical aspects implementing meta-heuristic approach: A case study - Mishra, Jyoti Prakash; Mishra, Sambit Kumar; Pólkowski, Zdzisław; Borah, Samarjeet (Analiza danych dotyczących aspektów klinicznych z wykorzystaniem podejścia metaheurystycznego: studium przypadku, 2021)
The application of information technology, particularly in health science in the present situation, is provisioned with intelligent applications along with automation to minimize the associated cost and enhancement of the facilities. Although the experimentation associated with the microorganisms may be a part of pathological aspects, it cannot be constrained at one specific location. Yet again, the same may be diversified widely in large geographical locations based on applications and utilities. The inclusion of computational intelligence along with complete advanced technical support is very necessary to overcome these difficulties and support the linked base stations for archiving optimum signals through the deployed sensors. In short, sensors can be used to translate the parametric values of accumulated data into signals which can also be analyzed and monitored. In this work, a specific meta-heuristic technique is implemented, focusing on the accumulation of sensors and the response time for accumulation of data.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 4 (62), s. 25-36
Keywords: clinical data; deployed sensor; virtual machines; swarm; processing elements; dane kliniczne; wykorzystane czujniki; wirtualna maszyna; rój; element przetwarzający